Why do people make risky decisions during a fire evacuation? Study on the effect of smoke level, individual risk preference, and neighbor behavior. (August 2021) - Fu, Meiqing; Liu, Rui; Zhang, Yu
Highlights: A risky evacuation decision is studies through an immersive VR-based experiment. A high smoke density reduces participants' use of a smoky shortcut. Individuals with high risk tolerance are more likely to evacuate through smoke. Neighbor behavior influences whether to evacuate through smoke. Abstract: People make risky decisions during fire evacuations such as moving through smoke. However, the reasons behind such risk-taking decisions have not been investigated in controlled experiments. Using an immersive virtual reality (VR)-based controlled experiment, this study investigated the effect of smoke level, individual risk preference, and neighbor behavior on individual risky decisions to take a smoky shortcut for evacuations. In the present experiment, participants' risk tolerance was measured using questionnaires, and their route choices were recorded when they evacuated from a virtual building under different smoke scenarios. A high density of smoke reduced the use of a smoky shortcut but did not prevent some participants from using the shortcut. Participants with high-risk tolerance were more likely to take a risky shortcut. However, individual attitude towards risk is unstable; hence, the risk preference revealed in daily behaviors under a low-danger context may not reveal individual risky decisions in face of high hazards. Moreover, neighbor behavior also had a significant impact on participants' risky decisions. The implications of our findings on evacuation training and management and evacuation simulation models were also discussed.